ANALISIS PENGENDALIAN DEMAM BERDARAH DENGUE (DBD) DI WILAYAH KERJA PUSKESMAS TIGO BALEH KOTA BUKITTINGGI - Nurdin Nurdin; Rani Imelda (EcoNews, 2019)
In 2016 in the city of Bukittinggi found as many as 106 cases of dengue, with IR = 84.99 100,000 population, there were 2 deaths with CFR of 1.8%. This condition is still far from the target of the Ministry of Health for the IR rate of <55 / 100.000 population and CFR <1%, so the case of DHF in City of Bukittinggi is high, the highest DHF cases are in the work area of Tigo Baleh Public Health Center as many as 26 cases. (DKK BKT Profile, 2016). The purpose of this study to find out information about policies, funding, human resources and facilities in the implementation of control dengue in the working region of health centre Tigo Baleh city of Bukittinggi.This research uses Qualitative method, with the approach of case studies. The informant of this research is 6 people, done by purposive. Data analysis is done through three stages:1. data reduction, 2. display data, 3. conclusion and perification.The results showed that the implementation of DHF control has been supported by the policy, insufficient human resources, sufficient funds, adequate facilities, PSN has not been maximal, discovery and relief activities have not run optimally, epidemiological investigation is not running maximally, monitoring and valuation carried out less maksumal. Aedes aegypti mosquito larvae control was obtained ABJ = 88,8%, that mean not reaching ABJ target set (≥ 95%)